Modulation of gut microbiota by Mantequilla and Melipona honeys decrease low-grade inflammation caused by high fructose corn syrup or sucrose in rats. (January 2022) - Coutiño-Hernández, Diana; Sánchez-Tapia, Mónica; Leal-Vega, Francisco; Bobadilla del Valle, Miriam; Ledezma, Héctor; Cervantes, Ricardo; Pedraza-Chaverri, José; Granados-Portillo, Omar; Díaz, Daniel; Antunes-Ricardo, Marilena; Gutiérrez-Uribe, Janet; Maya, Otoniel; et al.
Graphical abstract: Highlights: Mantequilla (MtqH) or melipona (MelH) honeys contain phenolics compounds and flavonoids associated with an antioxidant and antibacterial activity. The consumption of MtqH or MelH honeys modifies the intestinal microbiota, particularly a group of bacteria of the Clostridium genus. MtqH or MelH honeys promote anti-inflammatory response by increasing sIgA and decreasing LPS and NF- κB. MtqH or MelH honeys prevent glucose intolerance and reduces adipocyte size. Abstract: Several studies have shown that consumption of honey is associated with various health benefits. However, there is scarce evidence on whether honeys modify the intestinal microbiota by preventing the inflammatory response in the host. Therefore, the aim of the present work was to study the effect of Melipona (Mel) and Mantequilla (Mtq) honeys, which contain different bioactive compounds and antioxidant capacity on gut microbiota and metabolic consequences in comparison with other sweeteners, in particular sucrose (S) and high fructose corn syrup (HFCS) in rats. The results of the present work showed that both honeys have polyphenols, flavonoids, antioxidant and bactericidal activities. Rats fed with both honeys gained less weight and body fat by increasing energy expenditure compared to S or HFCS and increased gene expression of antioxidant enzymes mediated by the transcription factor Nrf2. Analysis of the gut microbiota showed that consumption of both honeys modified the beta-diversity compared to those fed S or HFCS resulting in increased abundance of a specific cluster of bacteria of the Clostridium genus particularly Coprococcus eutactus, Defluviitalea saccharophila, Ruminicoccus gnavus and Ruminicoccus flavefaciens . As a result of the changes in the gut microbiota, there was a decrease in LPS- and TLR4-mediated low-grade inflammation and an increase in sIgA. Consumption of both honeys prevented glucose intolerance and increased adipocyte size compared to S or HFCS. In conclusion, consumption of MtqH or MelH can reduce metabolic endotoxemia by modifying the gut microbiota to prevent glucose intolerance.